Peluang dan Tantangan Initial Public Offering (IPO) Pada Perusahaan Start-Up di Indonesia - Anggi Purnama Harahap; Rahmad Ramadhan Hasibuan; Lupitta Risma Candanni (Indonesian Journal of Islamic Economics and Business, 2020)
This paper will discuss the initial public offering (IPO) for startup companies. Case study of PT Aplikasi Karya Anak Bangsa Go-Jek. The discussion in this paper will emphasize startups and their comparison with IPOs in ordinary companies (Case Study PT Jasa Armada Indonesia, Tbk) and other startup companies, namely PT Kioson Commercial Indonesia, Tbk) in 2017. A qualitative approach with normative descriptive and benchmark method is used to analyze the problem mention above. This research finds that in general, public regulations and general guidance in Law Number 8 of 1995 concerning the Capital Market and other related regulations sufficient to meet the requirements of going public for public companies. But with the development of startup companies in Indonesia, especially PT Aplikasi Karya Anak Bangsa (Go-Jek), planning to conduct an initial public offering encourages the government to immediately make decisions on the initial public offering process rules so that these arrangements will not only reach ordinary companies with the number of assets large but also able to reach start-up companies to contribute to the development of the national economy.